2021
DOI: 10.3390/life11050389
|View full text |Cite
|
Sign up to set email alerts
|

Use of Anti-Diabetic Agents in Non-Diabetic Kidney Disease: From Bench to Bedside

Abstract: New drugs were recently developed to treat hyperglycemia in patients with type 2 diabetes mellitus (T2D). However, metformin remains the first-line anti-diabetic agent because of its cost-effectiveness. It has pleiotropic action that produces cardiovascular benefits, and it can be useful in diabetic nephropathy, although metformin-associated lactic acidosis is a hindrance to its use in patients with kidney failure. New anti-diabetic agents, including glucagon-like peptide-1 receptor (GLP-1R) agonists, dipeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 134 publications
(151 reference statements)
0
8
0
Order By: Relevance
“…Inhibitors or blockers of the renin-angiotensin system are generally considered preferable due to specific effects on glomerular hemodynamics [ 2 ]. Similar favorable effects on glomerular dysfunction are ascribed also to antidiabetic drugs inhibiting the sodium-glucose transporter-2 [ 3 ] and to reduced protein intake [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitors or blockers of the renin-angiotensin system are generally considered preferable due to specific effects on glomerular hemodynamics [ 2 ]. Similar favorable effects on glomerular dysfunction are ascribed also to antidiabetic drugs inhibiting the sodium-glucose transporter-2 [ 3 ] and to reduced protein intake [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several substrates might contribute to the pleiotropic action of DPP-4 inhibitors. The antiinflammatory, antioxidative, and antiapoptotic actions of DPP-4 inhibitors are mediated via GLP-1-dependent and GLP-1-independent mechanisms [72]. The involvement of GLP-1-independent mechanisms were similarly reported, the renoprotective effects of DPP-4 inhibitors were observed to a similar extent, in GLP1R-/knockout mice, compared with wild-type mice [19].…”
Section: Discussionmentioning
confidence: 78%
“…This effect was partly attributed to regulating ROS/p38MAPK/ERK and stimulating PI3K/AKT pathways [70]. However, it was shown that in the rat remnant kidney model, SIT improved renal functional and morphological changes by attenuating activation of the PI3K/AKT pathway [71,72]. These conflicting results have been related to different strains used and different experimental model induced in these studies.…”
Section: Discussionmentioning
confidence: 96%
“…It cleaves a wide variety of substrates, including the incretin hormones glucagon-like peptide-1 (GLP-1) and gastric inhibitory peptide (GIP), cytokines, and growth factors. It also acts as a binding protein and a ligand of extracellular factors [ 18 , 30 , 31 , 32 ], hence the pleiotropic effects of DPP-4 enzyme [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ]. Some indirect anti-inflammatory effects of DPP-4i may be mediated by GLP-1-dependent mechanisms as well, since GLP-1 also exerts anti-inflammatory properties [ 16 , 30 ].…”
Section: Discussionmentioning
confidence: 99%